PSYCHOLOGICAL ISSUES OF TEACHERS' PREPARATION FOR PROFESSIONAL ACTIVITY IN MODERN TIMES - Khuda-Zade, Konul (Revista Gênero e Interdisciplinaridade, 2026)
The article studies the psychological issues of teachers’ preparation for professional activity. The study studies the psychological issues of students’ preparation for and attitude to the teaching profession of different specialties using various methodologies and questionnaires. 76 students studying at Azerbaijan State Pedagogical Universities and having different professional orientations participated in the study. It was found that preparation for professional activity is determined, first of all, by psychological readiness, and internal and external factors play an important role here. The study showed that among the components of preparation for the profession preferred in education, effectiveness, efficiency, intention and positive attitude are most distinguished. The obtained results allow us to identify some guidelines for further study of students’ psychological preparation for the teaching profession as a scientific problem and to develop special psychological assistance and social support programs for novice teachers. The study showed that for students with high practical activity and academic abilities, preparation for the teaching profession is characterized by practical and initiative styles, and for those with low academic and practical abilities, by practical and managerial qualities.